2020
DOI: 10.21203/rs.3.rs-80682/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Plant Growth Promoting Rhizobacteria Microbial Inoculants on the Growth, Rhizosphere Soil Properties, and Bacterial Community of Pinus sylvestris var. mongolica Annual Seedlings

Abstract: [Objective] Determine the ability of three plant growth promoting rhizobacteria (PGPR) strains (Pseudomonas Mandelli A36, Serratia plymuthica A13 and Pseudomonas koreensis A20) to promote plant growth, evaluate the effect of inoculation with PGPR strains on seedling biomass, root structure, nutrient index, and enzyme activity, and assess the effect of PGPR inoculation on soil nutrient index, enzyme activity, and the soil microecological environment.[Method] The ability of the three PGPR strains to secrete indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Although these genera are already present in soil [37], it is still unknown how they affect plant health. On the other hand, we observed an increase in Pseudolabrys which is included in the phylum proteobacteria [38] and Uncul-tured_Acidobacteriales in both C10 and C12 samples linked to promoting plant growth [39]. Moreover, a study by Cipriano et al [40] and Chen et al [41] showed that there was an increase in abundance of Pseudolabrys when a plant growth promoting bacteria was used for inoculation.…”
Section: Discussionmentioning
confidence: 50%
“…Although these genera are already present in soil [37], it is still unknown how they affect plant health. On the other hand, we observed an increase in Pseudolabrys which is included in the phylum proteobacteria [38] and Uncul-tured_Acidobacteriales in both C10 and C12 samples linked to promoting plant growth [39]. Moreover, a study by Cipriano et al [40] and Chen et al [41] showed that there was an increase in abundance of Pseudolabrys when a plant growth promoting bacteria was used for inoculation.…”
Section: Discussionmentioning
confidence: 50%